Training Needs Identification of Agricultural Extension Agents in Wadi Zabid of Tihama Region, Yemen - Khalil, Ali Hassan O. (Journal of Agricultural Extension Management, 2019)
This study explored and described the in-service training needs of agricultural extension agents in Wadi Zabid of Yemen. Using a structured questionnaire, data were collected from forty one (n=41) randomly selected extension agents. Based on the Borich Needs Assessment Model, a survey of 40 competencies from previousresearch was developed to identify training needs of extension agents (n=41). Mean and standard deviation were calculated to report extension agents’ perceived level of performance and ability to practice for each professional competency, while mean weighted discrepancy scores (MWDS) were calculated to indicate inservice training needs.Findings revealed that the mean age of the respondents was 42.3 years. 31.7 percent of them have a Bachelor’s degree in agriculture and more than half (51.2 %) of the respondents had been working in extension services for 18 years. In addition,73.2 per cent of the extension agents were male and 26.8 per cent were female.Furthermore, the findings of this study reported that the most important competencies for extension agents were understanding the farming and production system(M=4.78); communicating farmers’ problems to researchers (M=4.73); understanding the duties and responsibilities at district and village level (M=4.70); understanding rural culture(M=4.70) and understanding the educational learning process of extension education (M=4.65). However, the findings showed that the highly rated in-service training needs were,producing print-based products (MWDS= 16.38); searching information on the internet(MWDS=15.7); preparing power point slides (MWDS=15.43); using e-mail (MWDS=14.88); using word processing software (MWDS=14.01 ); using flip chart flash cards(MWDS=12.56); operating film projector (MWDS= 12.25) and evaluating the effectiveness of extension visual-aids respectively(MWDS= 11.95).